Insignificant difference in medication adherence to dyslipidemia drugs between visually impaired and non-disabled people in South Korea: A nationwide cohort study using claims records - Jong Wook Lee; Hankil Lee; Euna Han; Hye-Young Kang (PLoS ONE, 2025)
Incidence of visual impairment (VI) and dyslipidemia is increasing with aging. Although good medication adherence (MA) is a crucial factor in achieving therapeutic goals for dyslipidemia, there is a paucity of studies measuring MA in the visually impaired with dyslipidemia. We investigated whether patients with VI had worse MA to dyslipidemia drugs than non-disabled people and determined the factors affecting MA among patients with VI. Data on dyslipidemia patients with VI were extracted in 2017 from the sample cohort database of the National Health Insurance Service. MA to dyslipidemia drugs was measured for two years based on the proportion of days covered (PDC). Conditional logistic regression analysis was performed to analyze the effect of VI on good MA (PDC ≥0.8). The VI group (0.860) had a larger PDC than the non-disabled group (0.850). The adjusted odds ratio (aOR) for good MA among VI vs. non-disabled individuals was statistically insignificant (1.137, 95% confidence interval:0.958–1.350). Significant factors for poor MA in the VI group were younger age (aOR for 20–39 vs. ≥75 years old: 0.124), lower income (aOR for 9-10th decile (rich) vs. 1-4th decile (poor): 1.771), shorter duration of dyslipidemia (aOR for 1–4 vs. 15 years: 0.416), having lower-level providers sas their main providers (aOR for clinics vs. general/tertiary-care hospitals: 0.545), and having mental diseases (aOR: 0.679). Patients with VI did not have worse MA than non-disabled patients taking dyslipidemia medication.